2022
DOI: 10.2196/36029
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions of Telemedicine Use During the COVID-19 Pandemic in Riyadh, Saudi Arabia: Cross-sectional Study

Abstract: Background The term “telemedicine” refers to the use of communication technology to deliver health care remotely. The COVID-19 pandemic had substantial impacts on health care delivery from 2020 onward, and it was necessary to adapt high-quality care in a manner that limited the potential for viral exposure of both patients and health care workers. Physicians employed video, phone, and electronic written (e-consultation) visits, all of which provided quality of care comparable to that of face-to-fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…These findings align with the recent research by [35], where 70% of 362 doctors from Riyadh, KSA affirmed that they are skilled at telemedicine, and 54% said they can independently solve technological issues during telemedicine visits.…”
Section: Computer and English Language Self-efficacy (Cese)supporting
confidence: 89%
“…These findings align with the recent research by [35], where 70% of 362 doctors from Riyadh, KSA affirmed that they are skilled at telemedicine, and 54% said they can independently solve technological issues during telemedicine visits.…”
Section: Computer and English Language Self-efficacy (Cese)supporting
confidence: 89%
“…In addition, telehealth caused a problem for physicians due to constant access by patients and intrusion into physicians’ private lives. This finding reverberated what other researchers found, as they argued that there is a problem of overreach and burnout when access to healthcare personnel is granted [ 28 30 ].…”
Section: Discussionmentioning
confidence: 53%
“…This study included most of the community populations with their different specialties. Other studies on telemedicine were associated with COVID-19, and this factor may have some influence on the results given that people during the pandemic tried to avoid visiting health care services, gave attention and used other methods for medical consultation and treatment, such as telephone calls and online contact with their physicians [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that 70% (n=254) of responding physicians believed that telemedicine consultations are cost-effective. Regarding burnout, 4.1% (n=15), 7.5% (n=27), and 27.3% (n=99) of the doctors reported feeling burnout every day, a few times a week, and a few times per month, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation